Life Quality Improvement of PLWHA through the Combined Peer and Family Supporting Model - Mahdalena, Mahdalena; Mahpolah, Mahpolah; Ramie, Agustine; Suroto, Suroto (International Journal Labs, 2023)
People living with HIV / AIDS (PLWHA) have been facing several problems such as the physiological problems as well as the stigma and discrimination that can increase their psychological burden. This study aimed to analyze the combined supporting model on the quality of life of PLWHA in RSUD dr. H.Ansari Saleh Banjarmasin. This study was an observational study, by observing the quality of life of PLWHA who are assisted in the VCT Poly Hospital of dr. H. Ansari Saleh Banjarmasin. The sample of this study were PLWHA who were registered at dr. H. Ansari Saleh Banjarmasin. This study used purposive technique with inclusion criteria, PLWHA who was first diagnosed as HIV positive by a physician, adult, can read and write and willing to be a respondent. Exclusion criteria for PLWHA aged < 19 years. The results showed that peer and family supporting model by peer and family were significant that affected the quality of life of PLWHA so if the two models are combined, it can be used to assist PLWHA.